The importance of forest cover for fish richness and abundance on the Amazon floodplain - Lobón-Cerviä, Javier; Hess, Laura Lorraine; Melack, John M.; Araújo-Lima, Carlos Alberto Rego Monteiro (Hydrobiologia, 2015)
Flooded forest is one of the most important fish habitats in Neotropical rivers, and one that is increasingly subjected to negative impacts from logging, agriculture, and other human activities. The purpose of our study was to test quantitatively whether fish richness and abundance in Amazonian floodplain lakes are associated with the area of flooded forest. We sampled fish and several other variables in 35 Amazonian floodplain lakes during the high-water season. Our results highlighted that fish richness and abundance were directly related to flooded forest, inversely related to distance from the river, and influenced by dissolved oxygen concentration <1 mg l−1. The same result applied to fish richness and abundance landed by fisheries. Other variables such as depth and area of open water habitat were also related but the results were less consistent and apparently reliant on sampling methodology. Our results suggest that conservation of the flooded forest is critical for the maintenance of fish assemblages in the Amazon, and that removal of flooded forest will reduce fish richness, fish abundance, and fisheries yield. © 2014, Springer International Publishing Switzerland.